A retro‐prospective effectiveness study on 3448 implant operations at one referral clinic: A multifactorial analysis. Part II: Clinical factors associated to peri‐implantitis surgery and late implant failures. (8th September 2017) - Jemt, Torsten
Abstract: Background: Little knowledge is available on implant treatment in large effectiveness studies in routine practice. Purpose: To report retro‐prospective data on prevalence of peri‐implantitis surgery and late implant failures in a large number of routine patients at 1 referral clinic. Materials and methods: Altogether 9582 implants with an anodized surface (Nobel Biocare AB) were consecutively placed between 2003 and 2011 and followed‐up to end of 2015. All peri‐implantitis operations and late implant failures were consecutively identified. A logistic multivariate data analysis was performed to identify association between the complications and different clinical factors. Furthermore, data on prevalence on risk for inflammation and bone loss at implants ("peri‐implantitis") and surgery related to peri‐implantitis was collected for another reference group of about 10 000 implant patients during 3 consecutive years (2013‐2015). Results: Cumulative survival rates for implant operations without peri‐implantitis surgery or implant failures were calculated to 96.4% (95% CI: 97.3‐95.4) and 95.0% (95% CI: 96.0‐94.1) after 10 years, respectively. Risk for "peri‐implantitis surgery" showed a significant association ( P  < .05) to number of placed implants (hazard ratio [HR] 1.40; 95% CI: 1.24‐1.59). Three factors showed significant association to risk for "late implant failures, " where "treatment in lower jaw" had the highest risk; HR 2.03. "Overall implant failures" were associated to 4 significant factors where "surgeon" (HR 2.50) showed highest impact on risk. "Numbers of implants" and "bone resorption" at surgery were the 2 significant factors that were consistent for all the time periods of failures during follow‐up (early/late/total). On an average 7.4% of examined patients in the reference group were denoted with highest risk group ("peri‐implantitis") of which on an average 12.7% of these patients had surgery related to peri‐implantitis. Conclusions: "The dentist" involved in the surgical and prosthetic rehabilitation of the implant patients, "number of implants" and degree of "bone resorption" seem to have most impact on overall implant complications and failures in the present patient group.